Analysis of Circular Waste Using a Causal Loop Diagram (CLD): A Case Study of Sukabumi City: Studi Kasus Kota Sukabumi - Eneng Rahmi; Lioba Evita Anikusuma (Postgraduate, University of Mataram, 2026)
This study examines the transition from linear to circular municipal solid waste management in Sukabumi City using a system dynamics approach. Utilizing a qualitative descriptive design, data were gathered through surveys of 400 residents across 33 villages, field observations of waste facilities, and stakeholder interviews. Results reveal significant